Morfologi Malai Padi (Oryza sativa L.) pada Beragam Aplikasi Pupuk Nitrogen - Rahayu, Sherly; Ghulamahdi, Munif; Suwarno, Willy Bayuardi; Aswidinnoor, dan Hajrial (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2018)
The effects of nitrogen fertilizer on agronomic and morphological characters depend on several factors such as genotypes and nitrogen rate. The study was aimed to evaluate nitrogen effects on rice panicle. A field experiment was conducted at Babakan Research Station during November 2015- February 2016 using a split-split plot design with three replicates. Nitrogen doses was a main plot, genotypes was a subplot, and time of application was a sub-subplot. A greenhouse experiment was carried out at PAIR, Jakarta during February-July 2017 using a completely randomized design with three replicates. The results from the field experiment indicated that the highest panicle number (13.25), number of filled grains (177.94) and spikelet number (213.76) were obtained at doses of 450 kg urea ha-1. Analysis of variance showed that the genotypic effects were significant for all traits observed, while the interaction effect between genotypes and time of nitrogen application was significant on the length of first grain from first node. However, the three-factors interactions were not significant for all traits. The greenhouse experiment revealed that both genotypes and N rates significantly affected all traits except for panicle number and the length of first grain from first node, respectively, while their interaction only significant for number of primary branch. Nitrogen increased all traits observed except the length of first grain from first node. Simultaneously, both experiments showed significant effects of genotypes for all traits observed. Doses of urea fertilizers above 400 kg ha-1 could improve the performance of panicle traits in order to increase yield potential.